Feedback Control Variables Have No Influence on the Permanence of a Discrete N-Species Cooperation System - Liujuan Chen; Xiangdong Xie; Lijuan Chen (Discrete Dynamics in Nature and Society)
A new set of sufficient conditions for the permanence of a discrete N-species cooperation system with delays and feedback controls are obtained. Our result shows that feedback control variables have no influence on the persistent property of the discrete cooperative system, thus improves and supplements the main result of F. D. Chen (2007).